Back to Square One. Green Sacrifice Zones in Sápmi and Swedish Policy Responses to Energy Emergencies - Össbo, Åsa (Arctic Review on Law and Politics, 2023)
In the wake of the enthusiasm for green energy, previously contested energy and mining projects can be framed as part of a green transition. When state authorities decide to forego the standard procedural protections and the processes and forums for deliberation and local influence, it contributes to constructing green sacrifice zones. This paper compares two Swedish energy policy processes. The first is occurred during World War II and the hydropower expansion of the 1940s and 1950s. The second takes place today when wind power is expanding to increase renewable energy production. In Sweden, policymaking seems to be back to square one in the green transition, leaving out both important knowledge of the past and contemporary voices of the ongoing and probable consequences. In certain issues, such as how the recognition of the Indigenous status of the Sámi actually affects the legislative process and how to address the Indigenous rights of the Sámi, policymaking is particularly slow to adapt. The green transition industry is already affecting the Sámi, as the construction of the Nordic welfare society has done during the last century, and still does. It deepens an ongoing colonial wave that started in the 1300s. By showing how the Swedish legislative process, historically as well as currently, has neglected to involve Sámi representatives, this study points to the importance and obligation of Swedish policymaking to engage Sámi representatives in an early phase to avoid further sacrifice zones in Sápmi.